A Learning Management Model to Enhance the Thai Communication Skills of Undergraduate Students - Boonprawes, Supasiri (ASEAN Journal of Education, 2023)
The research objective was to develop a learning management model to enhance the Thai communication skills of undergraduate students. The research instruments were 1) questionnaire of current and desirable conditions towards learning management for enhancing Thai language communication skills of undergraduate students. 2) Assessment form 3) Pre-study and post-study test in Thai communication for undergraduate students. The sample used for analysis from cluster sampling. The sample group were 40 1st - 2nd year level who were studying Thai language courses in the second semester of the academic year 2019 in Suan Dusit UniversityIt using cluster random sampling. The results revealed that 1.) A model of learning management to enhance Thai communication skills consists of 5 components: Principles, Objectives, Content, Learning management process, and Assessment. The results of the assessment and certification of a learning management model to enhance the Thai communication skills of undergraduate students was 4.84 at the most appropriate level. And 2) Undergraduate students who received this kind of learning model improved Thai language communication skills.